Phenomenologies of Shame - Pichon-Rivière, Rocío (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
This essay proposes a history of the concept of shame as it was articulated in the field of queer theory and more recently in Latin American trans theory. I propose phenomenological readings of texts in these traditions in light of classic phenomenologies of shame which found in this affective disposition an ontological structure: the subject’s openness to the other and to the social as such. If the conditions of possibility of the social as such depend on the ability of feeling ashamed, and if shame points sometimes though not always at an ethical or political norm, then this history of fenomenologies of shame could help us imagine the conditions of possibility of political change, through the works of Lawrence La Fountain-Stokes, Rubén Ríos Ávila, Marlene Wayar, Susy Shock y Clarice Lispector.
Keywords: Phenomenology of Shame; Individuation; Lawrence La Fountain-Stokes; Rubén Ríos Ávila; Marlene Wayar; Susy Shock; Clarice Lispector.